ASSESSMENT OF THE EFFECTIVENESS OF PUBLIC CIVIL SERVANTS OF THE RUSSIAN FEDERATION (THEORETICAL AND METHODOLOGICAL FOUNDATIONS) - D. Yu. Znamenskiy; A. V. Gusarov (Вестник университета)
The content of this article is an analysis of the theoretical and methodological foundations for assessing the professional and service activities of public civil servants in the Russian Federation. The relevance of the article lies in the fact that the ongoing process of transforming public administration and increasing demands from the population to public civil servants requires the development of new methods for of assessing the effectiveness of their activities in the Russian Federation for the successful selection of a modern civil servants who can comply with the growing requirements emanating from population and successfully cope with the assignments and tasks emanating from the country’s leadership. Different theoretical approaches of public administration researchers to assessing the effectiveness of public civil servants have been considered. An analysis of international experience in building and establishing a system for evaluating the effectiveness of public servants will highlight and implement elements of evaluating the effectiveness of public civil servants, taking into account legal, historical and social features of the Russian Federation.